The use of indocyanine green imaging technique in patient with hepatocellular carcinoma - Huang, Shih-Wei; Ou, Jing-Jim; Wong, Hon Phin (Translational Gastroenterology and Hepatology, 2018)
Near-infrared indocyanine green (ICG) fluorescence application in liver cancer surgery have been reported in the literature since 2008. To date, most reports emphasized not only to the safety, feasibility and reproducibility, but also the potential benefits of its clinical applications in term of demarcating segmentation for an anatomical resection, tumor identification to achieve tumor free resection margin, detection of small unidentifiable subcapsular nodules as well as extrahepatic metastatic lesions, and fluorescence cholangiography. The purpose of this review is to present the fundamental concept of the interpretation of fluorescence enhancement by different timing through intravascular ICG distribution to liver and biliary washout; to describe step-by-step technical aspects of its use in different purposes, and to expose the diagnostic and therapeutic perspectives of this innovative imaging technique in liver cancer surgery.